Coping with ambiguous relationships: Sex, tourism, and transformation in Cuba - Simoni, V. (Journal of Tourism and Cultural Change, 2014)
Relationships between foreign tourists and members of the visited population in Cuba tend to be ridden with ambiguities with regard to their instrumental and commoditized dimensions. In the realm of sexual encounters, these ambiguities become a source of moral controversy, as they call into question notions of ‘sex tourism’ and ‘prostitution’. Focusing on how foreign men travelling to Cuba account for sexual relationships with Cuban women, this article shows how a variety of notions of tourism and of being a tourist are played out to justify people's engagements. From the establishment of continuities between sexual seduction ‘at home’ and ‘on tour’, to the normalization of sex for money exchanges, to the quest for an ‘authentic Cuban sexuality’, different modalities and moralities of travel are actualized in tourists' narratives, alternatively silencing and highlighting transformations in the places, people, and conceptions of tourism. In addressing the question of what counts as ‘transformation’, this article sheds light on the situated and purposeful ways this notion is deployed, the controversies, and struggles it generates, as well as its moral underpinnings, affordances, and limits. Ultimately, this illustrates the interests of investigating change and notions of change in tourism in a reflexive and empirically grounded manner.